1993
DOI: 10.1079/bjn19930035
|View full text |Cite
|
Sign up to set email alerts
|

Diet and incident ischaemic heart disease: the Caerphilly Study

Abstract: The Caerphilly Prospective Ischaemic Heart Disease (IHD) Study is based on a sample of 2512 men aged 45-59 years when first seen. Nutrient intakes, estimated using a self-administered semi-quantitative food frequency questionnaire, are available for 2423 men (96 %). Amongst these, 148 major IHD events occurred during the first 5 years of follow-up. Associations were examined between these events and baseline diet. Incident IHD (new events) was negatively associated with total energy intake: men who went on to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 35 publications
4
70
2
1
Order By: Relevance
“…This study confirms in a Southern European population the inverse association found in studies from Northern Europe and the USA (Bolton-Smith et al, 1992; Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & BarrettConnor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999). Only a few studies, however, adjusted for energy intake and presented data separately for different types and sources of fiber.…”
Section: Fiber and Myocardial Infarction E Negri Et Alsupporting
confidence: 81%
See 2 more Smart Citations
“…This study confirms in a Southern European population the inverse association found in studies from Northern Europe and the USA (Bolton-Smith et al, 1992; Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & BarrettConnor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999). Only a few studies, however, adjusted for energy intake and presented data separately for different types and sources of fiber.…”
Section: Fiber and Myocardial Infarction E Negri Et Alsupporting
confidence: 81%
“…Several, mostly prospective, epidemiological studies, (Bolton-Smith et al, 1992;Burr & Sweetnam, 1982;Fehily et al, 1993;Humble et al, 1993;Khaw & Barrett-Connor, 1987;Kromhout et al, 1982;Kushi et al, 1985;Morris et al, 1977;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999) have investigated the relation between fiber intake and risk of acute myocardial infarction (AMI) or cardiovascular disease in general. Most have found significant inverse associations, although only a few have presented estimates adjusted for energy intake and separately for different types and sources of fiber (Kushi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire from each subject was carefully reviewed with a dietitian and further questions asked as necessary to ensure that the answers were complete and unambiguous. A 30% sample of the men were also asked to keep a 7-day weighed dietary intake record and data from these were used both to derive average portion sizes for use in the analysis of the questionnaires and to test the validity of the questionnaires (Fehily et al, 1987;Fehily & Hopkinson, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…First, the estimates of milk intake used in the analyses were derived from a semiquantitative food frequency questionnaire. In the interpretation of this, however, portion sizes were derived from 7-day weighed intake records kept in the cohort (Fehily et al, 1987;Fehily & Hopkinson, 1993). Moreover, the correlation between milk consumption as recorded in the 7-day weighed intake records provided by a subsample of 665 of the men, and as stated by those men in their questionnaires at baseline, was high (0.61; Po0.001).…”
Section: ; Vijvermentioning
confidence: 99%